Federalismo e Judicialização da saúde pública: o comportamento do Supremo Tribunal Federal no julgamento dos conflitos federativos sobre políticas públicas de combate à Covid-19. - Santos, Bruna Barboza Correia dos (2021)
Is the trend change observed in the judgment of federative conflicts related to the pandemic associated with the presence of federative categories? The direction against the central entity denoted a break with the historical tradition of the Supreme Court ruling in its favor. The dissertation hypothesizes that federalism is relevant to the result of each analyzed judgment, with the definition of a new decision-making standard of the Supreme Court in the assessment of federative conflicts. The study is justified by the need to monitor the evolution of federalism in the country, especially since, despite the model adopted, the effective distribution of political authority still suggests centralizing remnants of the Unitary State. Such importance grows in the face of the health crisis, in which federated entities should act in a coordinated and cooperative way. The research uses a qualitative method through the case study tool. Although the federative categories were relevant to the result of the judgments, it does not necessarily imply a new decision-making standard. Therefore, regardless of the importance of the federative foundation for decisions for decentralization, it is not possible to state that they reflect some evolution of federalism in Brazil. However, due to the recent and current position of the Union towards the potential deterioration of federative relations, it is possible to recognize that the result of the analyzed judgments represents the containment of a setback.